2015 7th International IEEE/EMBS Conference on Neural Engineering (NER) 2015
DOI: 10.1109/ner.2015.7146741
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal virtual reality platform for the rehabilitation of phantom limb pain

Abstract: Amputees usually perceive vivid awareness of their lost body parts after the amputation (phantom limbs). Phantom limb pain (PLP) is intense pain that is felt in the phantom limb. The mechanism of PLP is still unclear, but the major hypothesis is that it is derived from dysfunction of the brain. There are a few neurorehabilitation techniques using a mirror or virtual reality (VR) that present the visual image of a phantom limb to the patients, and this produce the movement perception of their phantom limb. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 13 publications
0
23
1
7
Order By: Relevance
“…Often medicalpharmacological analgesics are not able to alleviate phantom pain. Through our review, we found two studies Wake, et al, 2015) on PLP and VR neurorehabilitation. Both studies used…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Often medicalpharmacological analgesics are not able to alleviate phantom pain. Through our review, we found two studies Wake, et al, 2015) on PLP and VR neurorehabilitation. Both studies used…”
Section: Studymentioning
confidence: 99%
“…Oculus Rift and the same VR with small differences. This system could be applied to a future pain management platform offering flexible neurorehabilitation regimens for patients with PLP Wake, et al, 2015). Finally, Hoffman, et al, (2014) used Oculus Rift, for burn care with positive results.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Two were randomized controlled trials, eight were single group pre-test post-test without a control group comparison, seven were case series, and one was a case study. Eleven studies evaluated participants with upper phantom limb pain, [7,15,16,17,18,19,20,21,22,23,24] one study evaluated participants with upper and lower phantom limb pain. [25] One study evaluated upper limb complex regional pain syndrome, [26] one study evaluated lower limb complex regional pain syndrome, [27] and two studies evaluated upper and lower limb complex regional pain syndrome.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Movement of virtual limbs was controlled by movements of the affected (painful) limb in five studies [15,19,25,27,31] or movements of the non-affected (non-painful) limb in nine studies. [7,16,17,18,21,22,23,24,30] In one study a virtual arm was controlled by movement of the participant's affected (painful) arm but the virtual hand and fingers were controlled by the participant's non-affected (non-painful) hand and fingers. [26] In three studies participants did not control movement of virtual limbs but instead were required to imitate movements of a virtual limb, [20] and mentally imitate the movements of a virtual body.…”
Section: Treatment Characteristicsmentioning
confidence: 99%